2020
DOI: 10.1177/0272431620961457
|View full text |Cite
|
Sign up to set email alerts
|

Unsociability, Peer Rejection, and Loneliness in Chinese Early Adolescents: Testing a Cross-Lagged Model

Abstract: In this study, we explored the longitudinal linkages among Chinese early adolescents’ unsociability, peer rejection, and loneliness. Participants were N = 445 primary school students in Shanghai, P.R. China followed over 3 years from Grades 6 and 7 to Grades 8 and 9. Measures of adolescents’ unsociability, peer rejection, and loneliness were obtained each year from a combination of self-reports and peer nominations. Among the results, (1) compared with the unidirectional and bidirectional models, the cross-lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…In other words, peer phubbing was positively correlated with adolescent loneliness, which was, in turn, positively correlated with mobile social media addiction. Although previous research has demonstrated that peer rejection was closely associated with feelings of loneliness [ 26 , 27 ], no previous studies have tested the effect of peer phubbing. In the mobile internet era, peer phubbing has been the typical behavior of peer rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, peer phubbing was positively correlated with adolescent loneliness, which was, in turn, positively correlated with mobile social media addiction. Although previous research has demonstrated that peer rejection was closely associated with feelings of loneliness [ 26 , 27 ], no previous studies have tested the effect of peer phubbing. In the mobile internet era, peer phubbing has been the typical behavior of peer rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that peer rejection was one of the direct factors of adolescent loneliness. For instance, Xiao, Bullock, Liu, and Coplan found that peer rejection significantly contributed to the increase in loneliness [ 26 ]. Clear, Zimmer-Gembeck, Duffy, and Barber revealed that more frequent experience of peer victimization and rejection was associated with more loneliness [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the detrimental consequences of loneliness on adolescents’ mental health and daily functioning alongside the psychological and developmental characteristics of adolescents, it is crucial to understand the occurrence of loneliness at this sensitive period. Researchers have examined several antecedents of loneliness during adolescence, including personality traits (Zhang et al, 2015 ; Zhao et al, 2018 ), family and school environments (Li et al, 2019 ; Pengpid & Peltzer, 2018 ; Pilgrim & Blum, 2012 ; Yu et al, 2019 ), peer relationships (Carissa & Melanie, 2014 ; Xiao et al, 2021 ), and socioeconomic status (Chen & Chung, 2007 ; To, 2016 ). Physical characteristics and body image could also affect loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…Yet we know that many children are rejected, and even bullied, by their peers at school. Research has found that rejected children are at an increased risk of being badly treated by peers (Demol et al, 2020); often feel angry, sad, and lonely (Xiao et al, 2020;Zhang et al, 2014); and are more likely than other children to develop externalizing or internalizing problems (Ladd, 2006;Spilt et al, 2014;Sturaro et al, 2011). Moreover, the schoolwork of children and adolescents who are rejected and victimized by peers tends to deteriorate (Ladd et al, 2008;Liu et al, 2014).…”
mentioning
confidence: 99%
“…This stability seems to be due, at least in part, to the fact that children possess relatively stable physical or psychological characteristics that may trigger positive or negative reactions from peers. For example, compared to accepted children, rejected children tend to be either more aggressive or more withdrawn (Casper et al, 2020;Xiao et al, 2020). Accepted children, in contrast, tend to be socially skilled and display high levels of prosocial behavior, which makes them more attractive as friends and partners in peer play (McDonald & Asher, 2018;Slaughter et al, 2015).…”
mentioning
confidence: 99%